In vitro evaluation of fungicidal responses on the growth of pathogenic Rhizoctonia solani Kuhn, antagonistic binucleate Rhizoctonia and Trichoderma harzianum Rifai - Khandaker, Md Maniruzzaman; Bhuiyan, Md Khurshed Alam; Khair, Abul (Bangladesh Journal of Botany, 2010)
Two pathogenic isolates of Rhizoctonia solani Kuhn causing stem canker/black scurf disease of potato plants and four antagonist isolates, two of binucleate Rhizoctonia and two of Trichoderma harzianum Rifai were isolated from crop fields and evaluated in vitro for their fungicidal responses against eight fungicides. Vitavax was effective in inhibiting the growth of R. solani and binucleate Rhizoctonia but it did not inhibit the growth of T. harzianum at 100 ppm concentration. Terraclor Super X, Dithane M 45 and Boric acid are the fungicides which at 100 ppm concentration did not inhibit the growth of antagonist isolates of T. harzianum and binucleate Rhizoctonia but inhibited the growth of isolates of R. solani to some extent. The in vitro findings suggest that any one of these three fungicides along with antagonist isolates of binucleate Rhizoctonia and T. harzianum can be used as biocontrol agents to reduce soil borne inocula of R. solani. Key words: Rhizoctonia solani; Binucleate; Trichoderma harzianum; Fungicide DOI: 10.3329/bjb.v39i1.5534 Bangladesh J. Bot. 39(1): 107-110, 2010 (June)